USING HISTORIC POSTCARDS AND PHOTOGRAPHS FOR THE RESEARCH OF HISTORIC LANDSCAPE IN GEOGRAPHY AND THE POSSIBILITIES OF THEIR DIGITAL PROCESSING - Karol WEIS; Pavel HRONČEK (European Journal of Geography, 2017)
The paper analyzes basic possibilities of using old postcards and historic photographs in historic landscape research and presents basic methods of historic landscape elements analysis in geography and its related fields. The study is focused on the methods of selection of the appropriate historic images, as well as on their basic visual, formal and substantive assessment regarding geography and historical geography. The second part of the paper deals with the possibilities of digitization and subsequent digital modeling, resp. The virtual reconstruction of the contents of historic postcards and photographs using 2D and 3D models. Primarily, the relief and its temporal changes are modeled. Computer processing of the past landscape brings new, respectively derived information, which is not found or visible within other historical (archival) sources.